2021
DOI: 10.1515/rams-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic production and characterization of nickel–rhenium alloy coatings

Abstract: Electrolytic Ni–Re alloy coatings were obtained in galvanostatic conditions from nickel–rhenium baths with different contents of ammonium rhenate(vii) (0.5, 1.25, 2.5 and 5 g·L−1). The surface morphology, chemical, and phase composition of the obtained materials were determined. The coatings’ corrosion resistance tests were carried out in a 5% NaCl solution. Based on the tests, it was found that the highest corrosion resistance characterizes the coating with the highest rhenium content (37%). This material can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The reduction of the grains to nanometric sizes for electrochemically produced n-nickel increases the Vickers hardness from 140 to 650. It has also been observed that the nanocrystalline structure reduces the wear rate, increases corrosion resistance, and improves magnetic properties [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the grains to nanometric sizes for electrochemically produced n-nickel increases the Vickers hardness from 140 to 650. It has also been observed that the nanocrystalline structure reduces the wear rate, increases corrosion resistance, and improves magnetic properties [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain coatings with a thickness of 1-10 mm, aqueous electrolytes are the most promising. The use of solutions of various complex compositions [7][8][9] leads to the formation of alloys with a rhenium content in a very wide range, which implies a wide variety of surface functional properties that can be obtained by electroplating.…”
Section: Introductionmentioning
confidence: 99%